Psychological Distress During COVID-19 Curfews and Social Distancing in Saudi Arabia: A Cross-Sectional Study - Alghamdi, Badrah S.; Alatawi, Yasser; Alshehri, Fahad S.; Tayeb, Haythum O.; AboTaleb, Hanin; Binsalman, Amal (Frontiers in Public Health, 2022)
Background: Coronavirus disease 2019 (COVID-19) has spread to over 150 countries worldwide. Since the first case of COVID-19 was confirmed in Saudi Arabia, cases have continued to escalate exponentially. The COVID-19 outbreak has had a negative effect on mental health and well-being. The study aimed to investigate the effects of the strict national regulations associated with the COVID-19 pandemic on mental health. Methods: This was a cross-sectional study of a convenience sample of Saudi residents. Saudi residents aged 18 years or older were invited to complete an online questionnaire after one month of a nationwide 24-h curfew between May 6, 2020 and May 13, 2020. We measured psychological distress using the Depression, Anxiety, and Stress Scale-21 (DASS-21). We ran binary logistic regression analyses to detect variables that significantly predicted DASS-21 scores. Results: A sample of 2252 participants was recruited from the general population of Saudi Arabia. The DASS-21 score means and standard deviations for depression and anxiety for the whole sample (10.73 ± 10.29 and 6.98 ± 8.30, respectively) were in the range of mild depression and anxiety. In contrast, the mean DASS-21 stress score was within the normal range (11.97 ± 10.80). The mean stress score for healthcare workers was within the normal range (13.70 ± 10.68) but was significantly higher than the mean score for the public (11.56 ± 10.89; P = 0.0006). Several variables (e.g., age, gender, and history of contact with confirmed COVID-19 cases) were significantly associated with higher DASS-21 scores. Conclusions: The COVID-19 pandemic has created a psychological burden. Therefore, there is an urgent need to implement emergency public health interventions that ameliorate the risk perception of COVID-19 through the dissemination of adequate and targeted health information that could be a successful measure to mitigate the psychological impact of the Covid-19 pandemic.